A black phosphorus-based tunable Q-switched ytterbium fiber laser - Ahmad, Harith; Salim, Muhammad Aizi Mat; Thambiratnam, Kavintheran; Norizan, Siti Fatimah; Harun, S.W. (IOP Publishing, 2016)
A compact, passively Q-switched fiber laser with a tunable output is demonstrated. The proposed system uses a short length ytterbium doped fiber to create a very stable and compact optical circuit that uses black phosphorus (BP) as a saturable absorber to generate the desired short pulses. A stable Q-switch pulse train is obtained, with an operational wavelength range from 1056.6–1083.3 nm. Concurrently, a maximum pulse energy and minimum pulse width as well as a repetition rate range of 7.1 nJ, 4 μs and 6.0–44.8 kHz respectively was obtained. The proposed system will be able to cater to a multitude of applications that require a compact yet robust and cost-effective pulse laser.